“We Can Cope with the Pandemic”: Children’s Literature During Covid-19 - Awalyah, Wa Ode Zulhidjah; Hidayatun, Muthiah; Nurfaidah, Sitti (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
During the COVID-19 pandemic outbreak, many collections of children's literature with various subjects and genres were produced. This literary study aims to map the children’s literature published during the pandemic. This literary study aims to map the children’s literature published during the pandemic to inform the readers that various lists of children's literature can be freely accessed online according to their theme and genre without any boundary. The data was gathered by scrutinizing online collections of children's literature published in 2020 and 2021. Twenty-five pieces of children's literature were discovered. Using content analysis, this study revealed that the published literature fell into two categories, fiction, and nonfiction. The themes emerging in both categories include social community, family, heroes, health and science, and everyday life. In nonfiction, the most common themes are health and science, whereas, in fiction, the most common theme is family.